2017
DOI: 10.1177/1099800417692877
|View full text |Cite
|
Sign up to set email alerts
|

Variations in COMT and NTRK2 Influence Symptom Burden in Women Undergoing Breast Cancer Treatment

Abstract: Women with breast cancer frequently report distressing symptoms during and after treatment that can significantly erode quality of life (QOL). Symptom burden among women with breast cancer is of complex etiology and is likely influenced by disease, treatment, and environmental factors as well as individual genetic differences. The purpose of the present study was to examine the relationships between genetic polymorphisms within Neurotrophic tyrosine kinase receptor 1 (NTRK1), Neurotrophic tyrosine kinase recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Nurse scientists focus on understanding the biological underpinnings of symptoms that are inherently self-reported subjective phenomena and the extent to which they reflect or predict biological risk or vulnerability to changes in health. Several nurse scientists are conducting research that integrates precision health to better understand symptom burden, to predict or prevent disease, and to optimize individual treatment and quality of life improvement (Cashion, Gill, Hawes, Henderson, & Saligan, 2016; Cashion & Grady, 2015; Lyon et al, 2016; Tantoy et al, 2017; Young et al, 2017). For example, an intramural program of research at NINR is examining the underpinnings of symptom distress mechanisms in digestive disorders, specifically the biobehavioral relationships between inflammation and symptoms (Henderson, 2013).…”
Section: Precision Health Approaches For Advancing the Science Of Symmentioning
confidence: 99%
“…Nurse scientists focus on understanding the biological underpinnings of symptoms that are inherently self-reported subjective phenomena and the extent to which they reflect or predict biological risk or vulnerability to changes in health. Several nurse scientists are conducting research that integrates precision health to better understand symptom burden, to predict or prevent disease, and to optimize individual treatment and quality of life improvement (Cashion, Gill, Hawes, Henderson, & Saligan, 2016; Cashion & Grady, 2015; Lyon et al, 2016; Tantoy et al, 2017; Young et al, 2017). For example, an intramural program of research at NINR is examining the underpinnings of symptom distress mechanisms in digestive disorders, specifically the biobehavioral relationships between inflammation and symptoms (Henderson, 2013).…”
Section: Precision Health Approaches For Advancing the Science Of Symmentioning
confidence: 99%
“…However, in the present study, those observations were not statistically significant. Another bioinformatic analysis found MELK were related to worse OS in BC (Young et al, 2017). CLU might be a predictive factor for recurrence in <T2 stage BC (Yom et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NTRK2 , a direct target of miR-200c, codes for proteins expressed in mesenchymal or neuron-derived cells and may contribute to the relative risk for symptom burden during and shortly after the period of chemotherapy in women with early-stage breast cancer 4143. Li et al,44 using the gene microarray analysis, found that miR-105/93-3p activates Wnt/β-catenin signaling by the downregulation of SFRP1 , thereby promoting stem cells, chemoresistance, and TNBC cell metastasis.…”
Section: Discussionmentioning
confidence: 99%